2012
DOI: 10.1371/journal.pone.0041409
|View full text |Cite
|
Sign up to set email alerts
|

The Alveolin IMC1h Is Required for Normal Ookinete and Sporozoite Motility Behaviour and Host Colonisation in Plasmodium berghei

Abstract: Alveolins, or inner membrane complex (IMC) proteins, are components of the subpellicular network that forms a structural part of the pellicle of malaria parasites. In Plasmodium berghei, deletions of three alveolins, IMC1a, b, and h, each resulted in reduced mechanical strength and gliding velocity of ookinetes or sporozoites. Using time lapse imaging, we show here that deletion of IMC1h (PBANKA_143660) also has an impact on the directionality and motility behaviour of both ookinetes and sporozoites. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
102
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 33 publications
10
102
0
Order By: Relevance
“…The omission of the skin phase is unfortunate because the necessity of active parasite migration in the skin has opened up new opportunities for stopping the parasites before they enter the bloodstream, and skin migration may be an excellent drug and vaccine target. Indeed, sporozoite mutants with motility defects are significantly more attenuated after inoculation into the skin compared to after intravenous inoculation [16][17][18][19]. Similarly, parasite mutants defective in cell traversal activity, the sporozoite capacity to wound and transmigrate a host cell, also show impaired progression in the skin [20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The omission of the skin phase is unfortunate because the necessity of active parasite migration in the skin has opened up new opportunities for stopping the parasites before they enter the bloodstream, and skin migration may be an excellent drug and vaccine target. Indeed, sporozoite mutants with motility defects are significantly more attenuated after inoculation into the skin compared to after intravenous inoculation [16][17][18][19]. Similarly, parasite mutants defective in cell traversal activity, the sporozoite capacity to wound and transmigrate a host cell, also show impaired progression in the skin [20][21][22].…”
mentioning
confidence: 99%
“…The capacity to actively migrate is clearly important for sporozoite entry into hepatocytes [19,32]. However, fast and robust motility is only needed in the skin because diminished motility still allows sporozoites to effectively enter the liver if they are injected by syringe directly into the bloodstream [16][17][18][19]21,33]. This suggests that the malaria parasite has evolved a high speed specifically to cross the dermis, a finding that might well be important in intervention considerations that target their motility.…”
mentioning
confidence: 99%
“…In addition to these scaffolding proteins and the anchoring components of the motility apparatus that reside in the IMC, many additional proteins are known to occupy the pellicle or IMC domain butmost have yet to be characterized. [20][21][22].The importance of pellicle architecture in structurally supporting normal parasite motility has been demonstrated by several studies in which disruption of pellicle components has led to altered gliding behavior [23][24][25][26].…”
Section: Apicomplexan Architecturementioning
confidence: 99%
“…A productive forward translocation of the parasite, at a rate of ~1 to 3µm/sec, can be accomplished with either a circular gliding motility or a rotation-driven helical gliding behavior, though the latter appears to be the more important mode of movement as the parasite approaches and invades a potential host cell [40] (Fig 2a). Parasitesmay also anchor themselves at their posterior poles and engage in a seemingly non-productive vertical twirling behavior [40].However, when motility is observed within amore appropriateenvironment such as intact host tissue or even artificial,three-dimensional matrices, the movement patterns exhibited by parasitesin vitro translate into more of an irregular corkscrew-like motility that propels the parasitesin a somewhat curvilinear trajectory through the tissue [24][25][26][42][43][44][45] (Fig. 2b).…”
Section: Observations On Gliding Locomotionmentioning
confidence: 99%
“…In the genus Plasmodium , 13 conserved and syntenic alveolin family members have been identified that are differentially expressed among the three different zoites stages of malaria parasites [7], [8]. It has been shown in the rodent malaria species P. berghei that disruption of alveolins gives rise to morphological aberrations that are accompanied by reduced tensile strength of the zoite stages in which they are found [5], [8], [9], [10], [11]. In Tetrahymena thermophila , knockdown of the alveolin Tt ALV2 was also reported to affect cell morphology [12], indicating that alveolin functions, like their structures, are evolutionary conserved.…”
Section: Introductionmentioning
confidence: 99%